2005
DOI: 10.1002/esp.1227
|View full text |Cite
|
Sign up to set email alerts
|

Barchan ripples under unidirectional water flows in the laboratory: formation and planar morphology

Abstract: The purpose of the present study is to investigate the formation and planar shape of barchan ripples generated by laboratory unidirectional water currents and to compare the morphology with that of barchans formed by laboratory waves and flows in natural environments. A thin veneer of sand as a sediment source was placed initially at the upstream part of a recirculating flume and the change in bed configurations by the flow was recorded by a video camera. Two types of formative process were observed: one was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The confusion of the present state is exemplified by a recent study that explicitly compares the dune models of Werner and Nishimori with surface (impact) ripples in a wind tunnel experiment (Hatano et al, 2004). Although Endo et al (2005) have recognised differences in shape between subaerial dunes and current ripples, other quarters believe that experimental water flumes do indeed produce "dunes that are downsized copies of desert dunes" (Kroy and Guo, 2004). At the root of the debate must lie a fundamental question of sediment transport mechanisms: the relative roles of suspension, saltation, and creep in subaqeuous vs aeolian environments, as well as the impact of the fluid and fluid flow properties (e.g.…”
Section: Bare-sand Dunesmentioning
confidence: 93%
“…The confusion of the present state is exemplified by a recent study that explicitly compares the dune models of Werner and Nishimori with surface (impact) ripples in a wind tunnel experiment (Hatano et al, 2004). Although Endo et al (2005) have recognised differences in shape between subaerial dunes and current ripples, other quarters believe that experimental water flumes do indeed produce "dunes that are downsized copies of desert dunes" (Kroy and Guo, 2004). At the root of the debate must lie a fundamental question of sediment transport mechanisms: the relative roles of suspension, saltation, and creep in subaqeuous vs aeolian environments, as well as the impact of the fluid and fluid flow properties (e.g.…”
Section: Bare-sand Dunesmentioning
confidence: 93%
“…One implication of bedform-pattern development at the interacting-bedforms level is that it justifi es the use, for example, of water ripples as a proxy to address pattern development in aeolian dune fi elds (Hersen, 2005). Morphological and dynamic differences obviously exist between different types of bedforms in differing fl uids (Endo et al, , 2005. In hierarchy theory, however, these differences exist at the bedformfl ow level.…”
Section: Bedform Interactions Across System Types and Stagesmentioning
confidence: 98%
“…It is an important issue to understand the differences between subaqueous dunes and aeolian ones. Some morphologic relationships known for aeolian barchans are applicable also to aqueous barchans when appropriately rescaled, depending on the materials and fluids (Hersen et al, 2002;Endo et al, 2005;Claudin and Andreotti, 2006). Furthermore, Endo et al (2005) have reported some differences in the shapes of barchans that are attributable to differences in the sediment transport mechanism.…”
Section: Introductionmentioning
confidence: 94%